Transforming heterotrophic to autotrophic denitrification process: Insights into microbial community, interspecific interaction and nitrogen metabolism. (February 2022) - Huang, Xiao; Duan, Chongsen; Yu, Jianghua; Dong, Wenyi
Graphical abstract: Highlights: Transforming heterotrophic to autotrophic denitrification was feasible. NO2 − -N accumulation gradually occurred in the transformation process. The most complicated interspecific interaction was in heterotrophic process. EC1.7.2.2 promoted the enzymes abundance of NO2 − -N accumulation. Abstract: For investigating the microbial community, interspecific interaction and nitrogen metabolism during the transform process from heterotrophic to synergistic and autotrophic denitrification, a filter was built, and carbon source and sulfur concentration were changed to release the transformation process. The results demonstrated that the transformation process was feasible to keep nitrate nitrogen (NO3 − -N) discharge concentration lower than 15 mg L −1, however, nitrite nitrogen (NO2 − -N) accumulation and its rate reached 7.85% at initial stages. The dominant denitrification gunes were Methylophilaceae, Thiovulaceae and Hydrogenophilaceae for three processes, respectively, and the microbial interspecific interaction of heterotrophic denitrification was more complex than others. NO2 − -N accumulation was confirmed by the low abundance of EC1.7.7.1 and EC1.7.2.1, and the dominance degree of dark oxidation of sulfur compounds and dark sulfide oxidation improved in synthesis and autotrophic denitrifications.